Safety of the Peripheral Administration of Vasopressor Agents. (January 2019) - Lewis, Tyler; Merchan, Cristian; Altshuler, Diana; Papadopoulos, John
Vasopressors are an integral component of the management of septic shock and are traditionally given via a central venous catheter (CVC) due to the risk of tissue injury and necrosis if extravasated. However, the need for a CVC for the management of septic shock has been questioned, and the risk of extravasation and incidence of severe injury when vasopressors are given via a peripheral venous line (PVL) remains poorly defined. We performed a retrospective chart review of 202 patients who received vasopressors through a PVL. The objective was to describe the vasopressors administered peripherally, PVL size and location, the incidence of extravasation events, and the management of extravasation events. The primary vasopressors used were norepinephrine and phenylephrine. The most common PVL sites used were the forearm and antecubital fossa. The incidence of extravasation was 4%. All of the events were managed conservatively; none required an antidote or surgical management. Vasopressors were restarted at another peripheral site in 88% of the events. The incidence of extravasation was similar to prior studies. The use of a PVL for administration of vasopressors can be considered in patients with a contraindication to a CVC.